Logrando tus metas, la movilidad académica en la Facultad de Medicina. - Durante-Montiel, Irene; Islas-Upegui, Melissa M.; Fajardo-Dolci, Germán E.; Flores-Vázquez, Elsy Pamela; Bravo-Hurtado, Samuel; Flores-Vázquez, Ilse Mariana (Revista de la Facultad de Medicina de la UNAM)
The objective of this article is to describe the improvement strategies that the UNAM School of Medicine (FacMed), through the MAVI (Academic Mobility and Interinstitutional Linkage Unit), has implemented throughout its administration from 2016 to 2022. The situation of mobility in the Faculty of Medicine of the UNAM is discussed, as well as the personal and institutional benefits derived from academic mobility. Although academic mobility is an expensive situation that requires financing, the FacMed generated strategies and accompaniment with which mobility processes were carried out in its community. In addition, the programs that were created during the COVID-19 pandemic are described, in response to the continuous needs for internationalization, all of them adapted to geographical mobility limitations, such as the Virtual Language Exchange, to generate bilingual practices. Likewise, the Meet&Greet in Health Science Internationalization Program, an event where students from the UNAM Faculty of Medicine met with students from other higher education institutions, to discuss various research topics in health sciences. It should be noted that academic mobility at FacMed is not exclusive to the student community, since some teachers were also advised to be part of the UNAM program of special activities for inter-institutional cooperation (PAECI), which facilitated their stay or travel. out of the country.